PEMBELAJARAN KONSEP PECAHAN MENGGUNAKAN MEDIA INTERAKTIF BERBASIS MACROMEDIA FLASH BAGI SISWA SD PEMBANGUNAN V YAPIS WAENA, JAYAPURA - Titik Suparwati; Samuel A. Mandowen; Miftachul Jannah (LPPM Uncen, 2022)
In the world of education, a lot of knowledge is learned by students. One of them is Mathematics which has been taught starting from basic education to higher education. Fractions are a subject in the field of mathematics that is considered the most difficult to learn, both understanding the basic concepts and understanding the concept of their use, namely understanding operations in fractions. To overcome the above difficulties, in studying or teaching fractions to students about the concepts and operations of counting, it is necessary to have a method, so that learning mathematics becomes an exciting learning. One of them is the Interactive Media based on Macromedia Flash. The short-term objective of this service activity is to provide a new atmosphere for students in learning, namely introducing the use of Macromedia Flash-based Interactive Media in teaching fractions. Meanwhile, the long-term goal is for the teachers of SD Pemb.V Yapis Waena to obtain a new method for comparison in learning fractions. This activity was held on 18-19 September 2020 which was attended by 20 grade V students of SD Pemb.V Yapis Waena. The methods used are lectures, discussions, question and answer methods, demonstrations and practice, as well as observation and evaluation of the results of the multimedia teaching aids. The conclusion is that by learning the fraction concept using interactive media based on Macromedia Flash, the teacher will be more concrete in explaining the concepts and operations of fractions to students.Keywords: SD Yapis, Fractions, Method, Macromedia Flash